Relationship Between Physical Activity and Sedentarily Activity with Nutritional Status for Adults 20-39 years old in Malang - Khakim, Muhammad Irfan; Indria, Dewi Martha; Adiputra, Fancy Brahma (Universitas Respati Yogyakarta, 2022)
Nutritional problems are a public health problem that has been addressed as a global problem due to changes in lifestyle, such as decreased physical activity and the occurrence of a sedentary lifestyle. This study aimed to determine the relationship between physical activity and a sedentary lifestyle with adult nutritional status based on Body Mass Index. Analytical Observational Research with a cross-sectional approach on 380 adults aged 20-39 years in Malang City was conducted using the Global Physical Activity questionnaire and the Sedentary Behaviour Questionnaire. Bodyweight and height were measured as primary data. The levels of physical activity were low, medium, and high. Meanwhile, a sedentary lifestyle is divided into low, medium, and high categories. The nutritional status is measured with Body Mass Index (BMI). Â Data were analyzed by Kruskal-Wallis and Somers'D with a value of < 0.05 considered significant. The results showed the relationship between physical activity and nutritional status with a probability value of Sig = 0.002. The relationship between a sedentary lifestyle and nutritional status showed a probability value of Sig = 0.000. It indicates a significant relationship between physical activity and a sedentary lifestyle with adult nutritional status in Malang City. The correlation test results using Somer's D showed that the strength of the relationship between variables was very weak.Â There was a significant relationship between physical activity and a sedentary lifestyle with the nutritional status of adults in Malang City.